Practical M&A execution and integration a step by step guide to successful strategy, risk and integration management - McGrath, Michael, 1955- (Wiley corporate F & A., 2011)
"Covering the field of M&A execution, this accessible and practical book is divided into sections which broadly reflect the chronological order a typical M&A deal follows. Taking the reader through the M&A process, stage by stage, the book describes the challenges and goals for each, and suggests approaches to dealing with these challenges, presenting guidance on how to prepare for the stage. At each stage topics such as strategy, IT, communications, HR considerations and legal/regulatory constraints are addressed. Replete with practical tools such as process flows and sample control documents, the book also contains downloadable template control documents on an accompanying CD. The book also includes a number of interviews with those currently involved in M&A deals, industry perspectives from those outside the process, and is peppered with examples and over 30 case studies and examples. Covering the topic of M&A in general, the book also has a number of sections relating specifically to banking M&A in light of the unique nature of M&A in this industry and recent trends and activities in banking M&A"--